2022
DOI: 10.1038/s41467-022-29588-8
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of human islet cell type-specific identity genesets

Abstract: Generation of surrogate cells with stable functional identities is crucial for developing cell-based therapies. Efforts to produce insulin-secreting replacement cells to treat diabetes require reliable tools to assess islet cellular identity. Here, we conduct a thorough single-cell transcriptomics meta-analysis to identify robustly expressed markers used to build genesets describing the identity of human α-, β-, γ- and δ-cells. These genesets define islet cellular identities better than previously published ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 74 publications
8
51
0
Order By: Relevance
“…scRNA-seq of human islets cells and human pancreas has identified genes associated with Type 1 (T1D) and Type 2 diabetes (T2D) (5)(6)(7), genes important for islet cell development and maturation (8,9), for islet dysfunction and dedifferentiation (10,11), for aging (12), and genes involved in the transdifferentiation among islet cells (13,14). These studies typically use canonical gene sets to annotate different islet cell populations, but new gene sets are continuously identified that more precisely define islet cell subtypes as they passage from development, stem cell differentiation to maturation (15). scRNA-seq has also confirmed the presence of heterogeneity among human β-cells defining several β-cell subtypes with different gene profiles (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…scRNA-seq of human islets cells and human pancreas has identified genes associated with Type 1 (T1D) and Type 2 diabetes (T2D) (5)(6)(7), genes important for islet cell development and maturation (8,9), for islet dysfunction and dedifferentiation (10,11), for aging (12), and genes involved in the transdifferentiation among islet cells (13,14). These studies typically use canonical gene sets to annotate different islet cell populations, but new gene sets are continuously identified that more precisely define islet cell subtypes as they passage from development, stem cell differentiation to maturation (15). scRNA-seq has also confirmed the presence of heterogeneity among human β-cells defining several β-cell subtypes with different gene profiles (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…1f). Highly active transcription factors in SC-β cells include of RFX1, PDX1 and PAX6, which have been previously reported to be important for β-cell identity 27, 35 . Other highly active transcription factors, such as MAFG, EBF1, ISX, and PLAGL2, have not been highlighted in previous studies, demonstrating the utility of using both mRNA and chromatin accessibility data for identifying cell types.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the transcriptional similarity of our four pNET tumors to healthy, mature pancreatic islet cells, we scored malignant cells from each tumor with curated gene signatures specific to alpha, beta, gamma, and delta cells in mature human pancreatic islets ( Figure 2E )( 26 ). Tumor cells from pnet1 displayed robust expression of alpha cell and gamma cell gene signatures, with lower expression of the delta cell signature ( Figure 2E ); these findings are consistent with the robust expression of gamma and delta cell hormones PPY and VIP and elevated ARX TF activity identified in our previous analyses.…”
Section: Resultsmentioning
confidence: 99%